Association of prescribed medications with the risk of COVID-19 infection and severity among adults in South Korea - Huh, Kyungmin (Int J Infect Dis, 2021)
OBJECTIVES: Concerns have been expressed that some drugs may increase susceptibility to SARS-CoV-2 infection. In contrast, other drugs have generated interest as potential therapeutic agents. METHODS: All adults aged ≥18 years who were tested for COVID-19 were included. Exposure was defined as a prescription of study drugs which would have been continued until 7 days prior to test for COVID-19 or later. The outcome measures were the diagnosis of COVID-19 and severe COVID-19. Disease risk score matching and multiple logistic regression was used. RESULTS: Matched claims and testing results were available for 219,961 subjects, of whom 7,341 (3.34%) were diagnosed with COVID-19. Patients were matched to 36,705 controls, and the subset of 878 patients of severe COVID-19 also matched with 1,927 mild-to-moderate patients. Angiotensin receptor blockers were not associated with either the diagnosis of COVID-19 (adjusted OR [aOR], 1.02; 95% confidence interval [CI], 0.90–1.15) or severe disease (aOR, 1.11; 95% CI, 0.87–1.42). The use of hydroxychloroquine was not associated with a lower risk for COVID-19 (aOR, 0.94; 95% CI, 0.53–1.66) or severe disease (aOR, 3.51; 95% CI, 0.76–16.22). CONCLUSIONS: In this national claims data-based case-control study, no commonly prescribed medications were associated with risk of COVID-19 infection or COVID-19 severity.